Bifunctional oat products: Technology and nutritional effects - Gebhardt, Erich; Habel, Annedore; Dongowski, Gerhard; Drzikova, Barbora; Hampshire, Jörg (MTT, 2004)
The nutritional and health related benefits of oats and beta-glucans respectively are well-known. The implemenation of resistant starch into oats results in a bifunctional food containing factors for the reductions of the risk of coronary heart disease and additionally the risk of inflammatory diseases of the colon or even colon cancer. Materials included killned oat kernels (grinded), killned and steamed oat kernels (grinded), addition of corn starch, hiami corn starch, waxy corn starch, commercially available resistant starch, selected varieties (Marion, Hecht, Kanton). The investigations were made by small and industrial scale extrusion machines, partly with pre-conditioning. Moisture ranged from 15 to 30 %, temperature from 90 to 170. In contrary to barley and pea, resistant starch was not generated by extrusion of oat. The oil of oat blocks the introduction of effective amounts of mechanic energy during extrusion. Extrusion of variety Kanton, which is below 6 % oil, resulted in substantial resistant starch of 1.1 % d.b. Oat products with substantial contents of resistant starch in the range between 5 to above 10 % d.b. result by enrichment of oat or oat bran with hiami corn starch, optionally with commercially available resistant starch. Evidence was given to the formation of resistant starch at incompletely hydration. Heating of extrusion premix in an autoclav showed, that resistant starch is generated in substantial amounts by temperatures above 130 °C, dependent from heating time. The oil content influences the generation process. Autoclaving cycles enhance the generation of resistant starch. Bifunctional food products can be made by extrusion of mixtures of oat or oat bran (favored) and of hiami maize or other hiami botanical sources. The product properties, the quality characteristics and physiological effects give a good performance of shelf life, chewing properties or consumption preferences, binding of sterols and fermentation to SCFA, especially butyrate (in-vitro tests). Another possibility is the manufacturing of a butyrogenic product by co-extrusion.
Keywords: Ka; Oat product(s); composition; dietary fibre; resistant starch; butyrogeneity; sterol binding